Feeding ecology of the giant otter, Pteronura brasiliensis - Weber Rosas, Fernando Cesar; Zuanon, Jansen; Carter, Sarah K. (Biotropica, 1999)
The food habits of the giant otter, Pteronura brasiliensis, were determined by analyzing fecal samples collected year-round from communal latrines at Xixuau Creek (00°48'S, 61°33'W), Jauaperi River (central Brazilian Amazon) between 1993 and 1994. Communal latrines were also sampled during the low water season at Aquidauana River (19°32'S, 56°40'W), Pantanal of Mato Grosso do Sul (central Brazil). Fragments of vertebrae, mandibles, teeth, scales, and fin spines provided an estimate of the diet composition. Remains of fish were present in all of the samples. The main fish groups found at Xixuau Creek were Perciformes, represented specifically by Cichlidae (97.3% of all samples), Characiformes (86.5%) and Siluriformes (5.4%). The Characiformes were represented mainly by Erythrinidae (Hoplias sp. 90.6%), followed by Serrasalmidae (28%). The Anostomidae occurred with a frequency of 18.7 percent, while Characinae, Bryconinae, and Cynodontidae were only observed in 3.1 percent of the Characiformes records. At Aquidauana River, the Characiformes were the most frequent fish group, represented in 100 percent of all samples, followed by Siluriformes (66.6%) and Perciformes (33.3%). The fish from the main groups identified in the diet of the giant otters prefer riverbanks, lakes, and flooded forests. The feeding habits of Pteronura brasiliensis are probably influenced by the vulnerability and abundance of the prey consumed by this carnivore.
Keywords: Diet; Feeding Behavior; Mammal; Jauaperi River; Anostomidae; Bryconinae; Caesalpinia Ciliata; Carnivora; Characiformes; Characinae; Cichlidae; Cynodontidae; Erythrinidae; Hoplias Sp.; Lutrinae; Mammalia; Perciformes; Pteronura Brasiliensis; Pteronura Brasiliensis; Serrasalmidae; Siluriformes; Vertebrata